Tekanan Batin Tokoh Sama’ dalam Novel Bilād Bilā Samāʼ: Kajian Psikoanalisis Freud - Dia Sari; Imam Warmansyah; Isnaini Rahmawati (Ukazh : Journal of Arabic Studies, 2026)
Literary works, particularly novels, often represent the inner conflicts of characters shaped by social conditions and life experiences. In the novel Bilād Bilā Samāʼ by Wajdi al-Ahdal, the main character Sama’ is portrayed as experiencing psychological pressure due to social, cultural, and familial environments. This study aims to examine the inner psychological pressure of the character Sama’ through a literary psychology approach using the psychoanalytic theory of Sigmund Freud, which includes personality structure, psychological dynamics, and defense mechanisms. This research employs a qualitative descriptive method, with data collection techniques involving reading and note-taking, while the research data consist of words, phrases, sentences, and dialogues in the novel. The results indicate that psychological pressure shapes the character’s personality, making her tend to be reserved, stubborn, indifferent, vigilant, forgiving, and respectful toward her parents. Furthermore, the character Sama’ experiences neurotic and realistic anxiety, which triggers the emergence of defense mechanisms such as aggression, repression, displacement, and rationalization, with repression being the most dominant mechanism. The novelty of this research lies in the application of Freud’s psychoanalytic approach to reveal the character’s inner dynamics, contributing to a deeper understanding of the psychological complexity of characters in contemporary Arabic literature.